Metabolic surgery and iron homeostasis. (27th December 2018) - Benotti, Peter N.; Wood, G Craig; Still, Christopher D.; Gerhard, Glenn S.; Rolston, David D.; Bistrian, Bruce R.
Summary: Iron deficiency and anaemia after metabolic surgery, potentially modifiable nutritional complications, are becoming an increasing cause for concern as prevalence increases with time and there is limited evidence supporting the effectiveness of the current guidelines for prophylactic oral iron supplementation and treatment for deficiency. Abnormalities in iron nutrition predisposing to deficiency are common in severely obese patients, and the low‐grade systemic inflammation, also common to these patients, reduces the effectiveness of oral iron supplementation. The surgical procedures result in alterations of foregut anatomy and physiology, which limit iron absorptive capacity and daily food intake. These alterations and the limited effects of oral iron supplementation explain the high prevalence of postoperative iron deficiency and anaemia. This review outlines current mechanisms concerning the pathogenesis of disordered iron nutrition in patients with severe obesity, current gaps in knowledge, and opportunities for quality improvement.